2017
DOI: 10.1186/s12864-017-3668-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of reversible disulfide based on features from local structural signatures

Abstract: BackgroundDisulfide bonds are traditionally considered to play only structural roles. In recent years, increasing evidence suggests that the disulfide proteome is made up of structural disulfides and reversible disulfides. Unlike structural disulfides, reversible disulfides are usually of important functional roles and may serve as redox switches. Interestingly, only specific disulfide bonds are reversible while others are not. However, whether reversible disulfides can be predicted based on structural informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Besides the distance, the degree of solvent exposure infers oxidation susceptibility of the thiols. [45,47] We calculated the relative solvent accessibility (RSA) for all residues (Supporting Information, Table S1). There is one native Cys at the 27th site (C27) in TMV structure which is highly buried and has only 2 % RSA, consistent with its very poor reactivity in the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the distance, the degree of solvent exposure infers oxidation susceptibility of the thiols. [45,47] We calculated the relative solvent accessibility (RSA) for all residues (Supporting Information, Table S1). There is one native Cys at the 27th site (C27) in TMV structure which is highly buried and has only 2 % RSA, consistent with its very poor reactivity in the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…The longer distance apparently makes them hardly form disulfide bond. Besides the distance, the degree of solvent exposure infers oxidation susceptibility of the thiols . We calculated the relative solvent accessibility (RSA) for all residues (Supporting Information, Table S1).…”
Section: Figurementioning
confidence: 99%
“…Other important questions relate to the presence of cysteines and potential disulfide bonds in the protein (e.g., annotations in UniProt). Because of the importance of disulfide bonds for protein folding, stability, or complex formation, different computational methods have been described for working with them ( Sun et al, 2017 ; Gao et al, 2020 ). However, we should point out that some cysteines do not form disulfide bonds in natively folded proteins.…”
Section: Template Designmentioning
confidence: 99%
“… 253 Small-molecule diselenide bonds have been reported as having a bond length of 2.29 Å, 254 while disulfide bonds (in proteins) have a corresponding bond length of 2.05 Å. 255 It has also been suggested that van der Waals interactions and hydrogen bonding potential may also be important in determining inhibitory potency. 253 Diselenide 122 was a competitive inhibitor with a K i value of 15.7 μM.…”
Section: Inhibitors Of Racemases and Epimerasesmentioning
confidence: 99%